The attitude of Iranian students and instructors toward implementing EMI through virtual exchange - Rakhshandehroo, Mahboubeh; Rakhshandehroo, Zahra (Frontiers in Education, 2023)
English-medium instruction (EMI) has been rapidly adopted worldwide as a strategy for internationalization, accompanied by a substantial amount of research attention. However, research on EMI has only recently been conducted in Iran. To contribute to the ongoing growing literature, this study explores the attitudes of Iranian students and instructors toward the possibility of implementing EMI in Iran through virtual exchange (VE). In order to determine whether EMI can be used through VE in Iran, a mixed method sequential explorative study was conducted. It has been identified that the linguistic readiness of students and/or instructors is the primary barrier to the success of EMI through VE in Iran because EMI is still in its infancy. In accordance with the literature, systematic support is required at the institutional level. Yet many of the students showed interest in the idea of EMI via VE, even if it was only a short one-session VE lesson, primarily to enhance their linguistic skills and global competencies. This study proposes that integrating EMI through VE at the graduate level may be more feasible. This is because there are already more EMI seminars and classes available, students are self-directed learners, and they may be better linguistically prepared. Regarding EMI access through VE, there were advantages and disadvantages. The benefit of using VE in EMI is that EMI would be accessible even to students living in less privileged locations, but the disadvantage is that the accessibility of the Internet may not be stable, considering requiring a VPN to access some websites. It is hoped that this study will serve as a useful starting point for future research in Iran and similar settings.